The Political and Historical Dynamics of Nepal-India Relations - Kandel, Ishwori Prasad (Interdisciplinary Issues in Education, 2024)
This study examines Nepal’s political and historical relationship with India, focusing on key events that shaped their interactions. The purpose is to analyze how Nepal navigated its geopolitical challenges between India and China, particularly in the context of its foreign policies from the 18th century to the post-2006 revolution period. Using a historical-analytical methodology, the research draws on secondary sources to trace Nepal’s diplomatic and political strategies, emphasizing pivotal moments such as the 1950 Peace and Friendship Treaty, the 1962 Indo-China War, and the 1989 economic blockade. The findings reveal Nepal’s consistent struggle to maintain sovereignty while balancing Indian influence. The study highlights the implications of this relationship for Nepal’s political and economic strategies in the broader regional context, emphasizing its importance for future diplomatic policies.